Something smells bad to plant pathogens: Production of hydrogen sulfide in plants and its role in plant defence responses - Daniel Vojtovič; Lenka Luhová; Marek Petřivalský (Journal of Advanced Research, 2021)
Background: Sulfur and diverse sulfur-containing compounds constitute important components of plant defences against a wide array of microbial pathogens. Among them, hydrogen sulfide (H2S) occupies a prominent position as a gaseous signalling molecule that plays multiple roles in regulation of plant growth, development and plant responses to stress conditions. Although the production of H2S in plant cells has been discovered several decades ago, the underlying pathways of H2S biosynthesis, metabolism and signalling were only recently uncovered. Aim of the review: Here we review the current knowledge on the biosynthesis of H2S in plant cells, with special attention to L-cysteine desulfhydrase (DES) as the key enzyme controlling H2S levels biosynthesis in the cytosol of plant cells during plant growth, development and diverse abiotic and biotic stress conditions. Key Scientific Concepts of Review: Recent advances have revealed molecular mechanisms of DES properties, functions and regulation involved in modulations of H2S production during plant responses to abiotic and biotic stress stimuli. Studies on des mutants of the model plant Arabidopsis thaliana uncovered molecular mechanisms of H2S action as a signalling and defence molecule in plant-pathogen interactions. Signalling pathways of H2S include S-persulfidation of protein cysteines, a redox-based post-translational modification leading to activation of downstream components of H2S signalling. Accumulated evidence shows DES and H2S implementation into salicylic acid signalling and activation of pathogenesis-related proteins and autophagy within plant immunity. Obtained knowledge on molecular mechanisms of H2S action in plant defence responses opens new prospects in the search for crop varieties with increased resistance to bacterial and fungal pathogens.